1988
DOI: 10.1103/physreva.38.1207
|View full text |Cite
|
Sign up to set email alerts
|

Total-cross-section measurements for positron and electron scattering byO2,CH4

Abstract: Total cross sections (Qr's) have been measured for I -500-eV positrons and electrons scattered by 02, CH4, and SF6 using a beam-transmission technique. The positron Qr s are compared with the corresponding electron Qr's for each target gas. It is found that the positron Qr's are, in general, lower than the electron results. There are no prominent structures observed for positron scattering at low energies that would be comparable to the narrow shape resonances observed for electrons scattering from various mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(47 citation statements)
references
References 33 publications
7
36
4
Order By: Relevance
“…Experiments with weak positron sources usually require the use of strong magnetic fields, what increases the effective path length of projectiles in the gas cell, compare reference [76][77][78], so measured cross sections can be overestimated. On the other hand, wider apertures in scattering cell worsen the angular resolution, what underestimates cross sections in an energy-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments with weak positron sources usually require the use of strong magnetic fields, what increases the effective path length of projectiles in the gas cell, compare reference [76][77][78], so measured cross sections can be overestimated. On the other hand, wider apertures in scattering cell worsen the angular resolution, what underestimates cross sections in an energy-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2 we compare different determinations of atomic and molecular "radii" -experimental from viscosity, X-ray diffraction and self-diffusion measurements together with theoretical from self-consistent field calculations (for atoms) and present -from positron to- [79] (parameter-free model potential) and Zecca et al [74] (Schwinger multichannel). Experiments: Dababneh et al [76], Floeder et al [77], Sueoka and Mori [78] and Zecca et al [74].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7c shows calculations of elastic cross-sections for methane (CH 4 ) using two different values of rigid sphere radius: R 0 = 1.4632a 0 and R 0 = 1.5445a 0 . The use of smaller R 0 yields cross-sections consistent with DFT results using Boronski-Nieminen functional by Franz et al [10], while larger R 0 gives better agreement with old experimental datasets by Sueoka and Mori [79] and Dababneh et al [80]. On the other hand it is impossible with present approach to find R 0 allowing to reproduce TCS by Zecca et al [72].…”
Section: Molecular Targetsmentioning
confidence: 49%
“…To best [65], Zammit et al [66] and Fedus et al [3]; theories for N2: Elza et al [67], Carvalho et al [68], Tenfen et al [69], Mukherjee and Mukherjee [70] and Franz et al [10]; theories for CH4: Jain and Gianturco [71], Zecca et al [72] and Franz et al [10]. Experiments for H2: Fedus et al [3], Karwasz et al [51], Zecca et al [73] and Machacek et al [74]; experiments for N2: Hoffman et al [75], Sueoka and Hamada [76], Karwasz et al [51] and Zecca et al [77]; experiments for CH4: Floeder et al [78], Sueoka and Mori [79], Dababneh et al [80] and Zecca et al [72].…”
Section: Molecular Targetsmentioning
confidence: 99%
“…The total electron impact collision cross sections have been measured by Sokolov and Sokolova [1981] and Zubek et al [1981] for energies up to 10 eV, by Dababneh et al [1986] up to 50 eV, and by Szmytkowski and Maciag [1986] up to 100 eV. Recently, Zecca et al [1995] reported total cross section for electron scattering on SO2 in the energy range 90-4000 eV, which is in very good agreement with Szmytkowski and Maciag [1986] in the overlapping energy Table 1 The total e-SO2 collision cross section profile is presented in Figure 1, and the values at a few energies are given in The total elastic cross sections are fitted using the semiempirical formula [Zecca et al, 1995] a ( Table 1 at a few energy points.…”
Section: Totalmentioning
confidence: 99%